English Teachers Attitudes Towards Application of Continuous Assessment System - Dhakal , Milan (New Journey, 2023)
The article entitled "English Teachers Attitudes Towards Application of Continuous Assessment System" aims to find out English teachers’ attitudes towards application of Continuous Assessment System (CAS) and to discover the obstacles in using it. For these purposes the data are collected through the questionnaire selecting thirty English teachers from the ten schools of Chulachuli Rural Municipality of Ilam district in eastern part of Nepal. The selected teachers are trained and untrained, male and females and teaching in different levels. Both types of teachers are found to have positive and negative attitudes towards CAS. The teachers who are untrained and new have negative attitudes. But most of the teachers are found to have positive attitudes towards CAS. It is also found that the CAS is very effective tool of evaluation, and it is very necessary to integrate it with teaching learning activities.